2016
DOI: 10.1111/boj.12407
|View full text |Cite
|
Sign up to set email alerts
|

Environmental determinants of genetic diversity inCaragana microphylla(Fabaceae) in northern China

Abstract: The sand‐fixing shrub Caragana microphylla (Fabaceae) is extensively used for vegetation restoration in areas of northern China undergoing desertification. Although the understanding of its genetic variation and related determinants is an important component of plant conservation and ecological restoration in the face of a changing global environment, the relationship between genetic diversity in C. microphylla and climatic factors is unknown. In this study, we assessed population genetic variation in C. micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
(50 reference statements)
3
4
2
Order By: Relevance
“…Our study revealed that WI and SOP were the major environmental factors that affected genetic diversity indices of the 20 studied C. microphylla populations, which indicates that genetic variation in C. microphylla primarily depends on a greater than 5°C monthly mean temperature and SOP concentration. This result is not consistent with the previously reported relationship between ISSR diversity and environmental factors in C. microphylla from northern China (AP and CI were the major environmental factors that affected genetic diversity indices) (Huang et al., ). This suggests that AP and CI were the major environmental factors that affected genetic diversity indices in C. microphylla on the large‐scale field, and WI was the major environmental factors on the small‐scale field.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our study revealed that WI and SOP were the major environmental factors that affected genetic diversity indices of the 20 studied C. microphylla populations, which indicates that genetic variation in C. microphylla primarily depends on a greater than 5°C monthly mean temperature and SOP concentration. This result is not consistent with the previously reported relationship between ISSR diversity and environmental factors in C. microphylla from northern China (AP and CI were the major environmental factors that affected genetic diversity indices) (Huang et al., ). This suggests that AP and CI were the major environmental factors that affected genetic diversity indices in C. microphylla on the large‐scale field, and WI was the major environmental factors on the small‐scale field.…”
Section: Discussioncontrasting
confidence: 99%
“…In C. microphylla , we calculated a value of 0.5041 for I ; this is higher than the mean I value for outcrossing species produced by Bussell (). Compared with previous study, all values of genetic diversity indices estimated in C. microphylla in Horqin Sandy Land are higher than those reported in northern China based on ISSR analysis (Huang et al., ). These differences came from scale difference, because of Horqin Sandy Land was the main natural distribution area of C. Microphylla .…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…These results are in line with the relationship between genetic diversity and ecological parameters in Stipa grandis from Inner Mongolia (ZHAO et al, 2006). Also this point was considered by HUANG et al (2016) in Caragana microphylla (Fabaceae) with regard to relationships between climatic factors and genetic diversity that showed positive in uence of some climatic factors on genetic diversity. Similar to our results were reported in Artemisia halodendron (Asteraceae) that indicated by HUANG et al (2014).…”
Section: Discussionsupporting
confidence: 83%